KEMAMPUAN GURU MIPA MEMBUAT PENILAIAN PENGETAHUAN - Ningsih, Kurnia (Universitas Tanjungpura, 2016)
This research aims to describe MIPA teachers’ ability to design knowledge assessment through the analysis of achievement aspects of knowledge assessment. This research used a descriptive method with SMP MIPA teachers in Pontianak City who have taught for more than 5 years and have an undergraduate degree as the population. The samples in this research, selected using a purposive sampling technique, consisted of 12 teachers who submitted MIPA test items. The research instrument used the data of the test item document designed by the teachers in the form of a multiple-choice test. The data were analyzed descriptively which included data reduction, systematic data display, and conclusion. The results showed that of the 12 test instruments made by with 380 questions in total, the teachers’ ability to design knowledge assessment (Multiple Choice Questions) obtained 17.37% of knowledge aspect, 67.90% of understanding aspect, 8.68% of implementation aspect, and 6.05% of analysis aspect. There were no questions made related to evaluation and creation aspects. Keywords: teachers ability, designing knowledge assessment.